THE RELEVANCE OF COHERENCE - Daniela Gueiros Dias (Revista Direito Mackenzie)
The present article argues in favour of global coherence in judicial legal reasoning while criticizing ontological and justificatory coherence theories in law. It contends that the relevance of coherence is contingent upon the validity of a norm of coherence in any jurisdiction examined. The core claim of this article is that the relevance of coherence for judicial legal reasoning comes from its legal standing as provided by the content of the positive law of a particular jurisdiction (norm-oriented perspective). Such a norm-oriented perspective, so the article claims, might sustain a global notion of coherence in law. It all depends on the content of the positive law of a jurisdiction and on whether and how it posited the norm of coherence.